Path To a Healthy Work-Life Balance: Mobile Application for Work and Personal Life Mastery - Erfan Rahmani; Zarina Che Embi (Journal of Informatics and Web Engineering)
Drawing insights from diverse organizational methods, this study endeavors to facilitate effective self-development and organization in the face of contemporary demands as solutions for integrating goal tracking, event coordination, and task management within a unified calendar framework in a mobile application. There are three primary objectives of this study: firstly, to explore essential functionalities crucial for addressing the multifaceted challenges of modern life; secondly, to design and develop a mobile application that seamlessly integrates these functionalities; and finally, to evaluate the usability of the application through rigorous testing and feedback mechanisms. Envisaged deliverables include a fully functional mobile application designed to operate on the Android platform. Guided by the principles of agile software development, this study emphasizes continuous improvement and responsiveness to user needs throughout the development process. By adopting an iterative approach, the study aims to ensure the highest quality outcome, thereby enhancing the user experience and maximizing the application's efficacy in promoting work-life balance. Through this comprehensive approach, this study seeks to contribute to the ongoing discourse on work-life balance and offer practical solutions to individuals grappling with the complexities of modern living. By bridging the gap between organizational tools and personal development strategies, this study aspires to empower users in their pursuit of a harmonious and fulfilling lifestyle with a mobile application.